Neutrophil gelatinase-associated lipocalin does not originate from the kidney during reperfusion in clinical renal transplantation - Arie Passov; Minna Ilmakunnas; Marjut Pihlajoki; Kethe Hermunen; Marko Lempinen; Ilkka Helanterä; Villemikko Kailari; Markku Heikinheimo; Sture Andersson; Eero Pesonen (Intensive Care Medicine Experimental, 2021)
Abstract Background Acute Kidney Injury (AKI) is a common clinical complication. Plasma/serum neutrophil gelatinase-associated lipocalin (NGAL) has been proposed as a rapid marker of AKI. However, NGAL is not kidney-specific. It exists in three isoforms (monomeric, homo-dimeric and hetero-dimeric). Only the monomeric isoform is produced by renal tubular cells and plasma NGAL levels are confounded by the release of all NGAL isoforms from neutrophils. Our aim was to investigate whether NGAL is released into blood from injured renal tubules. Methods Kidney transplantation (n = 28) served as a clinical model of renal ischaemic injury. We used ELISA to measure NGAL concentrations at 2 minutes after kidney graft reperfusion in simultaneously taken samples of renal arterial and renal venous blood. Trans-renal gradients (venous–arterial) of NGAL were calculated. We performed Western blotting to distinguish between renal and non-renal NGAL isoforms. Liver-type fatty acid binding protein (LFABP) and heart-type fatty acid binding protein (HFABP) served as positive controls of proximal and distal tubular damage. Results Significant renal release of LFABP [trans-renal gradient 8.4 (1.7–30.0) ng/ml, p = 0.005] and HFABP [trans-renal gradient 3.7 (1.1–5.0) ng/ml, p = 0.003] at 2 minutes after renal graft reperfusion indicated proximal and distal tubular damage. NGAL concentrations were comparable in renal venous and renal arterial blood. Thus, there was no trans-renal gradient of NGAL. Western blotting revealed that the renal NGAL isoform represented only 6% of the total NGAL in renal venous blood. Conclusions Ischaemic proximal and distal tubular damage occurs in kidney transplantation without concomitant NGAL washout from the kidney graft into blood. Plasma/serum NGAL levels are confounded by the release of NGAL from neutrophils. Present results do not support the interpretation that increase in plasma NGAL is caused by release from the renal tubules.